2015
DOI: 10.1108/ijmpb-05-2014-0048
|View full text |Cite
|
Sign up to set email alerts
|

Where is intentionality in studying project delays?

Abstract: Purpose – In this paper, the dominant techno-rational view of studying delays in projects is challenged. In so doing, the purpose of this paper is to urge for more attention paid to studying the intentionalities of the planners involved in planning the schedule for projects. Design/methodology/approach – In this paper, the authors take a critical approach to review a range of literatures related to the concept of project delays. Through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 111 publications
1
12
0
1
Order By: Relevance
“…At the global level, an analysis of over 104 published research articles related to delays across 45 countries with the intention of identifying the universal top 10 causes of delays revealed that change orders, delays in payments to contractors, poor planning and scheduling, poor site management and supervision, incomplete design, inexperienced contractors, contractor's financial difficulties, owners financial difficulties, resource shortages, and poor labour productivity/shortage of skills were the top universal causes of construction delays (Zidane and Andersen, 2018). Eizakshiri et al (2015) have questioned the 'intentionality' of studying project delays, arguing that researchers are unaware of the intents of the planners involved in planning the schedule for projects. The authors urge researchers to look beyond the simple cause-andeffect ideology which currently manifests across current delay studies.…”
Section: Causes Of Delaysmentioning
confidence: 99%
“…At the global level, an analysis of over 104 published research articles related to delays across 45 countries with the intention of identifying the universal top 10 causes of delays revealed that change orders, delays in payments to contractors, poor planning and scheduling, poor site management and supervision, incomplete design, inexperienced contractors, contractor's financial difficulties, owners financial difficulties, resource shortages, and poor labour productivity/shortage of skills were the top universal causes of construction delays (Zidane and Andersen, 2018). Eizakshiri et al (2015) have questioned the 'intentionality' of studying project delays, arguing that researchers are unaware of the intents of the planners involved in planning the schedule for projects. The authors urge researchers to look beyond the simple cause-andeffect ideology which currently manifests across current delay studies.…”
Section: Causes Of Delaysmentioning
confidence: 99%
“…They state that organisations should place value on the identification of failures and shortcomings in this vain the authors suggest the use of Failure Modes and Effects Analysis (FMEA) as a suitable tool in the analysis of the system and the subsequent identification, categorisation and the mitigation of risks. Eizakshiri et al (2015) in their study state that in cases of delays in projects often the blame is pinned on the project plan or in the implementation of the plan. Instead the authors argue that the system itself must not be exempt from being the reason.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From the initiation to the closing stages, construction process especially that for megaproject development is complex and characterized by a number of uncertainties and inte (Brookes, 2015)ractions that can negatively influence the project delivery in many ways (Brookes, 2015;Dimitriou, 2014;Flyvbjerg, 2014;Flyvbjerg et al, 2003a;Mentis, 2015;Priemus, 2014;Renuka et al, 2014;Spirkova, 2014;Van de Graaf and Sovacool, 2014). For example, uncertainties about changes in weather conditions (Mentis, 2015), subcontractor delays (Diab and Nassar, 2012;Eizakshiri et al, 2015), community resistance (Jordhus-Lier, 2015), political interferences (Kennedy, 2015) and unpredictable site conditions (Adam et al, 2014;Boateng et al, 2012) can compromise the completion of megaproject development on time and on budget. Although economic and fiscal risks from natural disasters are quantifiable by using modern techniques, they remain difficult to incorporate into the megaproject decision-making process.…”
Section: Megaproject Risksmentioning
confidence: 99%